2016
DOI: 10.1370/afm.1886
|View full text |Cite
|
Sign up to set email alerts
|

Practical Opportunities for Healthy Diet and Physical Activity: Relationship to Intentions, Behaviors, and Body Mass Index

Abstract: PURPOSE Current strategies for improving diet and activity patterns focus on encouraging patients to make better choices, but they meet with limited success. Because the choices people make depend on the choices they have, we examined how practical opportunities for diet and physical activity shape behavioral intentions and achieved behaviors.METHODS Participants included 746 adults who visited 8 large primary care practices in the Residency Research Network of Texas in 2012. We used structural equation models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…16 Determining a patient's capability for health behavior change is based on an approach that emphasizes the actions and behaviors that individuals can actually do, their perceptions of the resources that are available in their community to support behavior change, and what they believe about the likelihood of being able to access them. 17,18 Ferrer and colleagues 17 demonstrated that the resources available for dietary behaviors were less predictive of intentions to eat a healthy diet relative to conversion factors that included barriers to and knowledge about healthy eating and having the time to prepare healthy meals. Both activity resources and conversion factors (eg, barriers, knowledge, and time), however, were significantly associated with intentions to be physically active.…”
Section: Discussionmentioning
confidence: 99%
“…16 Determining a patient's capability for health behavior change is based on an approach that emphasizes the actions and behaviors that individuals can actually do, their perceptions of the resources that are available in their community to support behavior change, and what they believe about the likelihood of being able to access them. 17,18 Ferrer and colleagues 17 demonstrated that the resources available for dietary behaviors were less predictive of intentions to eat a healthy diet relative to conversion factors that included barriers to and knowledge about healthy eating and having the time to prepare healthy meals. Both activity resources and conversion factors (eg, barriers, knowledge, and time), however, were significantly associated with intentions to be physically active.…”
Section: Discussionmentioning
confidence: 99%
“…The first 14 items of the instrument are dietary items and are categorized into four subscales: diet opportunity (items 1-5), diet barriers (items 6-8), diet knowledge (items 9-11), and diet time (items [12][13][14]. Physical activity is measured by the last eleven items of the CADA questionnaire and is grouped into three subscales: physical activity convenience (items 15-17), neighborhood (items [18][19][20][21][22], and physical activity barriers (items 23-25) [19].…”
Section: Instrumentmentioning
confidence: 99%
“…The gap between health-related intentions and health behaviors is exacerbated by several complex factors. For instance, in healthy diet, physical activity, hand washing and hygienic food handling (Ferrer et al, 2016; Fulham and Mullan, 2011), such gaps are evident. The intention/behavior gap in terms of health behaviors moreover depends on language barriers, a priori knowledge, user openness and interest, and user confidence (Chirawattanakij and Vathanophas, 2016).…”
Section: Introductionmentioning
confidence: 99%